Response to ‘reverse causality’ comment - Zhang, Shan; Wang, Hongwei; Ji, Jingjing; Chai, Ruiyu; Song, Shiyi; Shi, Jikang; Liu, Siyu (Cancer epidemiology, 2025)
This document is the authors' response to the received comments for manuscript CANEP-D-25-00912.